Abstract 14155: Haemodynamic Changes After Aortic Valve Replacement in Bicuspid Aortic Valve Disease Differ With Prosthesis Type - Bissell, Malenka M; Loudon, Margaret; Stoll, Victoria; Orchard, Elizabeth; Neubauer, Stefan; Myerson, Saul G (Circulation (New York, N.Y.), 2015)
IntroductionBicuspid aortic valve disease (BAV) is associated with dilatation of the proximal aorta and abnormal flow patterns, particularly increased helical flow and changes in the aortic wall shear stress. We assess the effect of different types of aortic valve replacement (AVR) on aortic flow patterns.HypothesisAortic valve replacement in bicuspid aortic valve disease normalises ascending aortic flow patterns.MethodsWe prospectively enrolled 87 participants27 BAV patients with prior AVR (10 mechanical, 8 bioprosthetic, 9 Ross procedure), 30 BAV patients with a native aortic valve and 30 healthy volunteers. All underwent 4D flow cardiovascular magnetic resonance.ResultsThe majority of patients with mechanical AVR or Ross showed a normalised flow pattern (70% and 67% respectively) with near normal rotational flow values (7.4±1.2 and 10.6±3.5 mm/s respectively; normal range -5 to +11 mm/s). They also showed reduced in-plane wall shear stress compared to native BAV (0.13±0.04 N/m for mechanical AVR vs. 0.37±0.05 N/m for native BAV, p<0.05). In contrast, all subjects with bioprosthetic AVR showed abnormal flow patterns (mainly marked right-handed helical flow), with similar rotational flow values to native BAV (20.7±3.3 mm/s and 25.9±3.1 mm/s respectively, p>0.05) and similar wall shear stress pattern. Data before and after AVR (n=16) supported these findingsmechanical AVR showed a significant reduction in rotational flow (29.3±5.3 to 7.9±1.2 mm/s, p<0.05) and in-plane wall shear stress (0.45±0.07 to 0.20±0.04 N/m, p<0.05), whereas these remained unchanged in the bioprosthetic AVR group.ConclusionsAbnormal flow patterns in BAV are significantly reduced after mechanical AVR or Ross procedure, but remain similar after bioprosthetic AVR. This is the first insight indicating that the type of valve replacement may influence post-operative aortic flow patterns, and could have important implications for future aortic growth.